2020
DOI: 10.24815/siele.v7i2.16768
|View full text |Cite
|
Sign up to set email alerts
|

A study of anxiety experienced by EFL students in speaking performance

Abstract: Many EFL students show anxiety when speaking English in Indonesia. Therefore, the researchers were interested to conduct this study to find out the level of English-speaking anxiety experienced by those students. In this quantitative study, data were collected from 29 students through a questionnaire that was adopted from the Foreign Language Classroom Anxiety Scale (FLCAS) consisted of 10 items developed by Horwitz, et al. (1986). The data from the questionnaire were analyzed by using the FLCAS questionnaire … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 12 publications
1
15
1
Order By: Relevance
“…According to Elwood et al (2012) , “trait anxiety is an individual’s tendency to appraise situations as threatening, avoid anxiety-provoking situations, and demonstrate high baseline physiological arousal” (p. 23). Erdiana et al (2020) indicated that trait anxiety, as a stable one, made people feel nervous in a wide range of situations. Situation-specific anxiety is a type of anxiety that is stimulated by a particular situation, for example, public speaking or participation in class ( Ellis, 1994 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to Elwood et al (2012) , “trait anxiety is an individual’s tendency to appraise situations as threatening, avoid anxiety-provoking situations, and demonstrate high baseline physiological arousal” (p. 23). Erdiana et al (2020) indicated that trait anxiety, as a stable one, made people feel nervous in a wide range of situations. Situation-specific anxiety is a type of anxiety that is stimulated by a particular situation, for example, public speaking or participation in class ( Ellis, 1994 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, studies indicate that EFL students, especially the ones in Indonesia, are still struggling in speaking performance. A study by Erdiana et al, (2020) shows that it is common to see students have difficulties and anxiety in recalling the words and respond to their teacher and other students when being asked to speak in English. Another study by Riadil (2020) demonstrates that students often make errors relating to grammar and vocabulary use, resulting in low English speaking performance.…”
Section: Introductionmentioning
confidence: 99%
“…Based on related literature, the students need a community to develop their speaking skills. Erdiana et al (2020) study has shown 65.52% of students will have low speaking anxiety if the teacher corrects students' mistakes. If the teacher gave the students appreciation, the student would have low language anxiety (Anggraeni et al, 2020).…”
Section: "My Heart Rate Is Racing My Friend Will Laugh At Me If I Spe...mentioning
confidence: 99%
“…YouTube can make students relaxed because the students can learn short learning via YouTube. Short-term projects or short learning in speaking could reduce speaking anxiety (Erdiana et al, 2020).…”
Section: "My Heart Rate Is Racing My Friend Will Laugh At Me If I Spe...mentioning
confidence: 99%
See 1 more Smart Citation